Metabolic Pathways Associated With Term Labor Induction Course in African American Women. Issue 2 (April 2020) - Carlson, Nicole S.; Frediani, Jennifer K.; Corwin, Elizabeth J.; Dunlop, Anne; Jones, Dean
Objectives: The purpose of this study was to evaluate differences in the metabolic pathways activated in late-pregnancy serum samples among African American women who went on to have term (≥37 weeks) labor induction requiring high total oxytocin doses to complete first-stage labor compared to those in similar women with low-oxytocin labor inductions. Study Design: Case–control study ( N = 27 women with labor induction with successful cervical ripening: 13 requiring the highest total doses of synthetic oxytocin to progress from 4- to 10-cm cervical dilation and 14 requiring the lowest total doses) with groups balanced on parity and gestational age. Serum samples obtained between 24 and 30 weeks' gestation were analyzed using ultra-high-resolution metabolomics. Differentially expressed metabolites between high-oxytocin induction cases and low-oxytocin induction comparison subjects were evaluated using linear regression with xmsPANDA. Metabolic pathways analysis was conducted using Mummichog Version 2.0, with discriminating metabolites annotated using xMSannotator Version 1.3. Results: Labor processes were similar by group with the exception that cases received over 6 times more oxytocin between 4- and 10-cm cervical dilation than comparison women. Induction requiring high total doses of synthetic oxytocin was associated with late-pregnancy serum levels of metabolites from the linoleate and fatty acid activation pathways in term, African American women. Conclusion: Serum levels of several lipid metabolites predicted more complicated labor induction involving higher doses of synthetic oxytocin to complete first-stage labor. Further investigation in larger, more diverse cohorts of women is needed to identify potential targets to prevent failed labor induction.